2013
DOI: 10.1371/journal.pone.0060949
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Surgical Outcome in Mesial Temporal Lobe Epilepsy Associated with Hippocampal Sclerosis Plus Neurocysticercosis: A Cohort Study

Abstract: BackgroundWhere neurocysticercosis (NCC) is endemic, chronic calcified neurocysticercosis (cNCC) can be observed in patients with mesial temporal lobe epilepsy associated with hippocampal sclerosis (MTLE-HS). Considering that both disorders cause recurrent seizures or cognitive impairment, we evaluated if temporal lobectomy is cognitively safe and effective for seizure control in MTLE-HS plus cNCC.MethodsRetrospective cohort study of neuropsychological profile and surgical outcome of 324 MTLE-HS patients submi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…The authors of this proposal speculated that inflammatory lesions or repetitive seizures might play a role in disease pathogenesis 17,18 . Additionally, although refractory epilepsy associated with TLE-HS plus NCC was previously believed not to influence surgical outcomes 19 , these patients achieved postoperative Engel IA statuses less frequently 20 . In the present study, we observed that a longer duration of epilepsy and the involvement of multiple lobes predicted worse seizure outcomes in patients with HS plus NCC.…”
Section: Discussionmentioning
confidence: 85%
“…The authors of this proposal speculated that inflammatory lesions or repetitive seizures might play a role in disease pathogenesis 17,18 . Additionally, although refractory epilepsy associated with TLE-HS plus NCC was previously believed not to influence surgical outcomes 19 , these patients achieved postoperative Engel IA statuses less frequently 20 . In the present study, we observed that a longer duration of epilepsy and the involvement of multiple lobes predicted worse seizure outcomes in patients with HS plus NCC.…”
Section: Discussionmentioning
confidence: 85%
“…23 Data from a tertiary care epilepsy surgical service in Brazil suggest that hippocampal atrophy in patients with NCC is related to repetitive seizure activity. [4][5][6] Although this is a plausible pathogenic trigger for hippocampal atrophy, it is difficult to draw broad conclusions from a population limited to cases of medically intractable epilepsy. A plausible alternative involves inflammation-mediated damage as the causative mechanism for hippocampal atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…3 Several clinical series and a few controlled studies suggest an association between neurocysticercosis (NCC) and hippocampal atrophy. [4][5][6][7] However, it is not yet clear whether this association is related to repetitive seizure activity or to mechanisms of local or remote inflammation. [8][9][10] We recently reported the association between calcified NCC and hippocampal atrophy in a population of 248 older adults living in rural Ecuador.…”
Section: Introductionmentioning
confidence: 99%
“…Information derived from a series of patients with medial temporal lobe epilepsy strongly suggest a cause-and-effect relationship between calcified NCC and hippocampal atrophy, on the basis of differences in the characteristics and severity of seizures among patients with both conditions when compared with those with hippocampal atrophy alone. [5][6][7] In this context, it has been suggested that calcified cysticerci lead to hippocampal atrophy by causing recurrent seizures or status epilepticus, and the resulting hippocampal atrophy-in turnexacerbates the seizure disorder. Parasites may not be necessarily located within limbic circuits, suggesting a remote deleterious effect of seizures on hippocampal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] An association between calcified NCC and hippocampal atrophy has also been suggested based on studies of patients with refractory epilepsy, but the actual prevalence and relevance of this association is largely unknown. [5][6][7][8] Here, we report the results of a populationbased and a nested case-control study aimed to assess the prevalence of calcified cysticerci and its association with hippocampal atrophy in community-dwelling elderly persons living in Atahualpa, a rural Ecuadorian village where NCC is endemic. 9 The study focused on individuals 60 years of age to cover the possibility that such association exists but take a long time to develop.…”
Section: Introductionmentioning
confidence: 99%